Does dexmedetomidine prevent colistin nephrotoxicity? - Talih,Gamze (2018)
Abstract Background In this study, we aimed to investigate the effect of dexmedetomidine on colistin nephrotoxicity in rats. Methods Thirty-two Wistar albino rats were allocated into four groups. Intraperitoneal (ip) saline at 1 mL.kg-1 was administered to the control group and 10 mg.kg-1 ip colistin was given to the colistin group. In the DEX10 group 10 mcg.kg-1 dexmedetomidine ip was given 20 min before the injection of 10 mg.kg-1 ip colistin. In the DEX20 group ip 20 mcg.kg-1 dexmedetomidine was injected 20 min before the administration of 10 mg.kg-1 ip colistin. These treatments were continued twice a day for seven days. Samples were taken on the eighth day. BUN, Cr, KIM-1, TAS, and TOS were examined in blood samples and caspase-3 was examined in kidney tissue samples. Results The values for BUN, Cr and TOS were significantly higher in the colistin group than in the control group. BUN, Cr and TOS changes in the DEX10 and DEX20 groups were not significant compared with the control group but they were significantly lower compared with the colistin group. TAS values in the DEX10 group were significantly lower than in the control group. Apoptotic activity was significantly higher in the colistin group compared with the control group, but there was no significant difference in terms of caspase-3 staining activity when DEX10 and DEX20 groups were compared with the control group. Conclusion Oxidative damage and apoptosis played roles in colistin nephrotoxicity, and colistin nephrotoxicity could be prevented by treatment with dexmedetomidine.